The Use of Heat From the Incineration of Municipal Solid Waste for Processing of Phosphogypsum - Krot, Olga; Vinnichenko, Varvara; ., . (International Journal of Engineering and Technology, 2018)
Municipal landfills and open dumps with industrial waste are global issues which impact on the environment and on the health of populations. The production of phosphoric acid from natural phosphate rock gives rise to an industrial by-product called phosphogypsum, containing mainly dihydrated gypsum. Five tons of phosphogypsum are generated per ton of phosphoric acid production. The technology of roasting of phosphogypsum in a dehydrator, which is a mine, has been described in the article. Such reprocessing of the waste makes it possible to obtain a ready-made high-quality building material. The development of a complex that processes wet and highly adhesive phosphogypsum using the heat of combustion of alternative fuel (municipal waste) is consistent with the synergetic concept of environmentally efficient utilization. Experimental studies identify the most rational parameters of the dehydrator, namely, its operating temperature, have been conducted. The temperature of a heat carrier (air) varied from175 °Cto350 °Cin the experiment.